The effect of oestrogen dose and duration in programmed frozen cycles on obstetric outcomes and placental findings. Issue 4 (April 2023) - Ganer Herman, Hadas; Volodarsky-Perel, Alexander; Nu, Tuyet Nhung Ton; Machado-Gedeon, Alexandre; Cui, Yiming; Shaul, Jonathan; Dahan, Michael H
Abstract: Research question: Does programmed frozen embryo transfer (FET) with high-dose oestrogen affect obstetric outcomes and placental findings? Design: A retrospective cohort of live singleton deliveries at a single institution between 2009 and 2017, including deliveries attained by IVF with programmed FET; oocyte recipients were excluded. High-dose oestrogen was defined as a daily dose >6 mg throughout treatment. All placentas were evaluated regardless of complication status and the Amsterdam classification was used to analyse findings. Results: A total of 57 deliveries in the high-dose oestrogen group were compared with 274 controls. The high-dose oestrogen group displayed significantly longer duration of oestrogen treatment (18.8 ± 4.9 versus 13.3 ± 2.7 days, P  < 0.001), total cumulative oestrogen dose (149.7 ± 46.1 versus 80.3 ± 16.8 mg, P  < 0.001) and lower endometrial thickness (8.5 ± 1.4 versus 9.8 ± 1.7 mm, P  < 0.001). After adjustment for confounders, higher dose oestrogen was found to be associated with a lower average birthweight (coefficient –252.4 g, 95% confidence interval [CI] –483.5 to –21.2), a higher rate of low-birthweight neonates (adjusted odds ratio [aOR] 4.88, 95% CI 1.05 to 22.57), bilobated placentas (aOR 3.36, 95% CI 1.04 to 10.89), accessory lobes (aOR 8.74, 95% CI 1.24 to 61.5), accelerated villous maturation (aOR 2.06, 95% CI 1.09 to 3.87), retroplacental haematoma (aOR 5.39, 95% CI 1.11 to 26.13) and maternal malperfusion lesions (aOR 1.46, 95% CI 1.04 to 2.05). Conclusion: A higher daily oestrogen dose in programmed FET is associated with low birthweight and placental changes, although this may relate to altered endometrial properties and not to the treatment itself.